ChroniclItaly and ChroniclItaly 2.0: Digital Heritage to Access Narratives of Migration. Issue 1 (October 2021) - Viola, Lorella
Abstract : Although the voice of migrants and minorities has increasingly being heard in migration research, studies of past narratives of migration remain comparatively rare. The reason for this lies in the fact that accessing historical records of migrants' personal accounts is technically difficult. Voicing the experiences and 'inner life' of migrants, the immigrant press represents a suitable compromise. This article presents ChroniclItaly (Viola 2018) and ChroniclItaly 2.0 (Viola 2019), two digital heritage collections of Italian immigrant newspapers published in the United States between 1898 and 1920. Both corpora include the digitized front pages of 4, 810 issues of seven Italian newspapers' titles and contain 16, 624, 571 words; ChroniclItaly 2.0, in particular, includes annotations for referential entities such as people, places and organizations. The material was collected from Chronicling America, an Internet-based directory of digitized newspapers published in the United States from 1789 to 1963. With their focus on the turn of the twentieth century, ChroniclItaly and ChroniclItaly 2.0 are valuable sources for studying past narratives of migration and for obtaining new insights into the migrants' role in the history of modern states. This article describes the context, rationale, data design and accessibility of the archives as well as research applications.